Preparation method and application of NiFe-LDH / CeO2 composite nanomaterial
By growing NiFe-LDH nanosheets on CeO2 nanowires, NiFe-LDH/CeO2 composite nanomaterials are formed, the problems of poor conductivity and insufficient catalytic ability of LDH materials are solved, and efficient glucose detection is achieved.
Patent Information
- Application Number
- CN202411432189.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The existing LDH materials have poor electrical conductivity, easy agglomeration and insufficient catalytic capabilities, resulting in limited application in glucose sensors.
By growing NiFe-LDH nanosheets on CeO2 nanowire cores, NiFe-LDH/CeO2 composite nanomaterials are formed, and the conductivity and catalytic performance of LDH are improved.
The electrocatalytic activity and electron transport capability of NiFe-LDH are improved, the catalytic performance of glucose is enhanced, and an electrochemical sensor with high sensitivity and good stability is achieved.
Smart Images

Figure CN119409235A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a NiFe-LDH / CeO 2 The invention relates to a preparation method and application of composite nanomaterials, belonging to the field of electrochemical sensors. Background Art
[0002] Diabetes is a chronic disease that develops when the pancreas does not produce enough insulin to regulate blood sugar or when the body cannot effectively use the insulin produced. If diabetes is not well treated, several other health problems may ensue, such as eye complications, foot complications, kidney disease, stroke, and heart disease. Strict control of blood sugar levels is essential to prevent or reduce diabetes and its complications. Regular monitoring of physiological blood sugar levels is essential to effectively treat and prevent any hyperglycemia or hypoglycemia.
[0003] Glucose biosensors are divided into two categories: enzymatic and non-enzymatic. Non-enzymatic glucose electrochemical sensors have shown great potential due to their advantages of low price, ultra-high sensitivity and low environmental dependence, and have received extensive attention and research. The selection of catalysts for non-enzymatic glucose sensors is a key factor affecting the sensitivity and selectivity of glucose detection. Nanomaterials are widely used in the construction of non-enzymatic glucose electrochemical sensors due to their large reactive surface area, good catalytic efficiency and strong adsorption capacity, such as precious metal nanomaterials (Au, Ag, Pd), transition metal materials (Ni, Cu), metal oxides (CuO, NiO), alloys (Pt-Pb, Pt-Cu), metal organic frameworks (MOFs) and layered double hydroxides (LDH).
[0004] Layered double hydroxide (LDH) is a type of two-dimensional material with a unique anionic layered structure. Its general formula is a brucite-like layer composed of divalent and trivalent metal ions (M(II) and M(III)). The chemical composition formula of LDH is [M II 1-x M III x (OH) 2 ] x+ A x / n n- .mH 2 O, where M II and M III are divalent and trivalent metal cations, respectively, M II The ion is usually Ca 2+ , Mn 2+ Mg 2+ , Fe 2+ 、Co 2+ 、Ni 2+ , Cu2+ or Zn 2+ etc., M. III It can be Al 3+ , Fe 3+ , Mn 3+ or Co 3+ etc. n- is an interlayer anion, such as CO 3 2- , NO 3- and Cl - etc., usually existing between layers together with crystal water. LDH is a classic electrocatalyst due to its large surface area, good adsorption capacity, high chemical stability and efficient anion exchange performance. These characteristics also make LDH widely used in electrocatalysis, adsorption, biosensing and energy storage. At present, a variety of LDHs have been used in electrochemical sensing platforms to detect small biological molecules such as hydrogen peroxide, lactic acid, ascorbic acid, glucose, etc., such as NiCo-LDH, NiFe-LDH, ZnAl-LDH, CoCu-LDH, NiAl-LDH, NiMn-LDH, etc. However, due to the inherent low conductivity of LDH materials, the slow diffusion of electrolytes, and the easy accumulation of interlayer electrostatic forces during the preparation process, resulting in the blocking of the inner surface of the material, the utilization efficiency of its active sites is reduced, which hinders the practical application of LDH-based materials in glucose sensors. Therefore, integrating LDH into various structures, such as active supports or frameworks, is considered to be beneficial not only for maintaining the structure of LDH but also for improving its electrocatalytic activity. In addition, fine-tuning the nanostructure morphology of LDH is also considered to be an effective strategy to increase the electrochemical surface area and further improve the exposure of active sites in electrocatalysis. Summary of the invention
[0005] In order to solve the problems of poor conductivity, easy agglomeration and insufficient catalytic ability of LDH materials in the prior art, one of the purposes of the present invention is to provide a NiFe-LDH / CeO 2 The preparation method of nanocomposite materials starts with the micromorphology design of the catalyst (LDH) and uses CeO 2 The excellent properties of nanomaterials, such as non-toxicity, biocompatibility, good chemical stability, high mechanical strength and good electron transfer ability, are used to modify NiFe-LDH to form a heterostructure, improve the stacking and conductivity of the NiFe-LDH structure, thereby enhancing its catalytic performance, and thereby make a modified electrode to obtain an electrochemical sensor with good electron transfer ability, good stability and high sensitivity. The NiFe-LDH / CeO 2 The preparation method of the nanocomposite material is as follows:
[0006] (1) CeO 2Preparation of nanowires: Ce(NO 3 ) 3 6H 2 O and NaOH were dissolved in deionized water to obtain Ce(NO 3 ) 3 6H 2 O solution and NaOH solution, and slowly drip the NaOH solution into the Ce(NO 3 ) 3 6H 2 O solution to obtain a mixed solution I, which was subjected to a hydrothermal reaction. After the reaction was completed, the mixed solution I was cooled to room temperature, the solid was collected and washed by centrifugation with ethanol, and then the obtained solid was dried. Finally, the dried solid was calcined to obtain white CeO 2 Nanowire powder;
[0007] (2)NiFe-LDH / CeO 2 Synthesis of nickel nitrate (Ni(NO 3 ) 2 6H 2 O), ferric nitrate (Fe(NO 3 ) 3 9H 2 O) and urea are dissolved in deionized water to form a mixed solution II; ammonium fluoride is dissolved in deionized water to form an ammonium fluoride solution; the ammonium fluoride solution is slowly added to the mixed solution II under continuous stirring to form a mixed solution III, and the stirring is continued, and then the white CeO obtained in step (1) is added to the mixed solution. 2 The nanowire powder was added to the mixed solution III to obtain a mixed solution IV, and the mixed solution IV was subjected to a hydrothermal reaction. The solid was collected and washed by centrifugation with ethanol, and finally the obtained solid was dried to obtain a brown solid powder NiFe-LDH / CeO 2 Nanocomposite materials.
[0008] Preferably, in step (1), Ce(NO 3 ) 3 6H 2 The molar concentration of the O solution is 5-15 mmol / L, and the molar concentration of the NaOH solution is 0.3-0.7 mol / L; the Ce(NO 3 ) 3 6H 2 The volume ratio of O solution to NaOH solution is 1:1 to 1:5.
[0009] Preferably, the hydrothermal reaction conditions in step (1) are 100-140° C. for 12-48 h; the calcination temperature is 300-700° C. for 1-5 h.
[0010] Preferably, in step (2), the total molar concentration of Ni and Fe metal ions in the mixed solution II is 5.4 mmol / L, wherein the molar concentration ratio of Ni ions to Fe ions is 1:1 to 4:1; the molar concentration of urea is 2.6 mol / L; the molar concentration of the ammonium chloride solution is 2 mol / L; the volume ratio of the ammonium fluoride solution in the mixed solution III to the mixed solution II is 1:1 to 1:7; the CeO in the mixed solution III is 1:1 to 1:7; 2 The added amount of nanowire powder is 0.5 mg / mL to 1.17 mg / mL.
[0011] Preferably, the hydrothermal reaction conditions in step (2) are 120° C. and the time is 12 h.
[0012] Preferably, the drying temperature in step (1) and step (2) is 50°C.
[0013] The second object of the present invention is to provide a NiFe-LDH / CeO 2 Application of nanocomposites in the preparation of electrode materials.
[0014] Preferably, NiFe-LDH / CeO 2 The nanocomposite material is prepared into a dispersion liquid, and the dispersion liquid is evenly dropped onto the surface of the electrode material.
[0015] Preferably, the dispersion is prepared by: mixing 1 to 5 mg of NiFe-LDH / CeO 2 The nanocomposite material is dissolved in 1 mL of a mixture of ethanol and water with a mass concentration of 0.00005% to 0.0002% of nafion, wherein the volume ratio of ethanol to water is 1:1. The mixture is ultrasonically treated for 30 minutes to prepare a uniform dispersion with a concentration of 1 to 5 mg / mL.
[0016] Preferably, the electrode material includes a glassy carbon electrode and a screen-printed electrode.
[0017] Preferably, the preparation method of the screen-printed electrode is as follows: polyvinyl chloride (PVC) is used as a flexible substrate, a screen printing plate is used as a mold, and a three-electrode system screen-printed electrode (SPE) is prepared by a high-temperature ink screen printing process, wherein the working electrode and the counter electrode are carbon electrodes, and the reference electrode is an Ag / AgCl electrode; the SPE electrode pretreatment method is an electrochemical treatment method, and in the presence of 0.1 mol L -1 Cyclic voltammetry was performed in PBS (pH 7.0) solution for 10 cycles at a scan rate of 0.05 V s -1 , the scanning range was 0-1.5 V, and then rinsed with distilled water to obtain the screen-printed electrode (SPE).
[0018] The third object of the present invention is to provide a NiFe-LDH / CeO2 Application of electrodes prepared from nanocomposite materials in the detection of glucose.
[0019] Beneficial effects of the present invention
[0020] (1) Compared with the traditional NiFe-LDH catalyst, the NiFe-LDH / CeO 2 Composite nanomaterials are CeO 2 Heterostructure of NiFe-LDH nanosheets grown on nanowire cores, interaction between solid-solid interfaces and CeO 2 The modification can effectively regulate the electronic structure of metal sites on the LDH surface and improve the electrocatalytic activity of the material.
[0021] (2) The present invention innovatively designs NiFe-LDH / CeO 2 Composite nanomaterials, including CeO 2 The good electron transport ability of the nanowires promoted the charge migration on the surface of NiFe-LDH, improved the problem of easy stacking of LDH, and enhanced the electron transport ability of the composite nanomaterials, greatly improving the catalytic performance of glucose.
[0022] (3) NiFe-LDH / CeO designed by the present invention 2 The composite nanomaterial modified electrode has excellent detection limit, sensitivity and stability for glucose detection, which broadens the application of LDH materials in the field of electrochemical sensors.
[0023] (4) Compared with the conventional electrode detection device, the NiFe-LDH / CeO 2 / SPE electrode has the characteristics of easy operation, cost-effectiveness, small size and portability, and rapid response, which is conducive to the rapid and portable detection of blood glucose and has broad market potential.
[0024] (5) The nickel-based metal used in the present invention has a high space utilization rate of up to 74.05%. The high utilization rate accelerates the catalytic glucose oxidation process, making the electrode material have excellent electrochemical properties; Fe-based materials are also widely used catalyst materials due to their low price, excellent redox ability, fast electron transfer speed and high catalytic activity. When combined with Ni-based materials, the synergistic effect of the two metals can further promote the catalytic oxidation of glucose by the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The CeO prepared in Example 1 2 、Ni 3 Fe 1 -LDH and Ni 3 Fe 1-LDH / CeO 2 Scanning electron microscope characterization image.
[0026] Figure 2 CeO prepared in Example 1 2 、Ni 3 Fe 1 -LDH and Ni 3 Fe 1 -LDH / CeO 2 X-ray diffraction spectrum of .
[0027] Figure 3 The different electrodes (CeO 2 / GCE, NiFe-LDH / GCE and NiFe-LDH / CeO 2 / GCE) in 0.1mol / L KCl and 5mmol / L [Fe(CN) 6 ] 3- / 4- Cyclic voltammograms and electrochemical impedance spectroscopy in electrolyte solutions, where Figure a shows different electrodes (CeO 2 / GCE, NiFe-LDH / GCE and NiFe-LDH / CeO 2 / GCE) in 0.1mol / L KCl and 5mmol / L [Fe(CN) 6 ] 3- / 4- Cyclic voltammograms in electrolyte solution; Figure b shows different electrodes (CeO 2 / GCE, NiFe-LDH / GCE and NiFe-LDH / CeO 2 / GCE) in 0.1mol / L KCl and 5mmol / L [Fe(CN) 6 ] 3- / 4- Electrochemical impedance spectroscopy in electrolyte solution.
[0028] Figure 4 The different electrodes (GCE, CeO 2 / GCE、Ni 3 Fe 1 -LDH / GCE and Ni 3 Fe 1 -LDH / CeO 2 (GCE) Cyclic voltammograms in the presence or absence of 0.5 mmol / L glucose.
[0029] Figure 5 The cyclic voltammograms of NiFe-LDH / GCE electrodes with different Ni:Fe molar ratios (1:1, 2:1, 3:1 and 4:1) against 0.05 mmol / L glucose in Example 1 and Example 2.
[0030] Figure 6 The different masses of CeO in Example 1 and Example 3 2 NiFe-LDH / CeO nanowires (30, 40, 50, 60, 70 mg) 2 Cyclic voltammogram of the composite nanomaterial to 0.05mmol / L glucose.
[0031] Figure 7 Schematic diagram of the screen-printed electrode (SPE) prepared in Example 4 and a schematic diagram of the screen-printed electrode detecting glucose, wherein Figure a is a schematic diagram of the screen-printed electrode (SPE); Figure b is a schematic diagram of the screen-printed electrode detecting glucose.
[0032] Figure 8 The NiFe-LDH / CeO prepared in Example 4 2 IT curves of the SPE electrode when different concentration gradients of glucose were continuously added at 0.55V.
[0033] Fig. 9 The NiFe-LDH / CeO prepared in Example 4 2 IT curves of the SPE electrode at 0.55 V with different analytes (50 μmol / L glucose, 0.5 mmol / L ascorbic acid (AA), 0.5 mmol / L L-cysteine (L-Cystrine), 0.5 mmol / L citric acid (CA) and 1 mol / L sodium chloride (NaCl)) added in 0.1 mol / L NaOH.
[0034] Fig.10 The four identical NiFe-LDH / CeO prepared in Example 4 2 / SPE electrode reproducibility test for glucose.
[0035] Fig.11 The NiFe-LDH / CeO prepared in Example 4 2 / Stability of SPE electrode for glucose detection within 7 days. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0037] Example 1
[0038] A Ni 3 Fe 1 -LDH / CeO 2The preparation method of the GCE electrode is as follows:
[0039] (1) CeO 2 Preparation of nanowires: 0.1 mmol Ce(NO 3 ) 3 6H 2 O and 0.015 mol NaOH were dissolved in 10 mL and 30 mL deionized water, respectively. The NaOH solution was slowly dripped into the Ce(NO 3 ) 3 6H 2 O solution to obtain mixed solution I, which was poured into a reactor and subjected to hydrothermal reaction at 120°C for 24 hours. After the reactor was cooled to room temperature, the solid was collected and washed three times by centrifugation with ethanol, and then the obtained solid was dried in an oven at 50°C overnight. Finally, the solid product was placed in a muffle furnace and calcined at 500°C for 3 hours to obtain white CeO 2 Nanowire powder.
[0040] (2)Ni 3 Fe 1 Synthesis of -LDH: 0.2 mmol of nickel nitrate (Ni(NO 3 ) 2 6H 2 O), 0.07 mmol of iron nitrate (Fe(NO 3 ) 3 9H 2 O) and 0.13 mol urea are dissolved in 50 mL of deionized water to form a mixed solution II; at the same time, 0.02 mol of ammonium fluoride is dissolved in 10 mL of deionized water to form an ammonium fluoride solution. The ammonium fluoride solution is slowly added to the mixed solution II under continuous stirring to form a mixed solution III, and stirring is continued for 0.5 hours. The mixed solution III is transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 120°C for 12 hours. The solid is then collected and washed three times by centrifugation with ethanol, and finally the obtained solid is dried in a vacuum drying oven at 50°C overnight to obtain a brown-yellow solid powder NiFe-LDH nanomaterial.
[0041] (3)Ni 3 Fe 1 -LDH / CeO 2 Synthesis: 0.2 mmol of nickel nitrate (Ni(NO 3 ) 2 6H 2 O), 0.07 mmol of iron nitrate (Fe(NO 3 ) 3 9H 2O) and 0.13 mol urea were dissolved in 50 mL of deionized water to form a mixed solution IV; at the same time, 0.02 mol of ammonium fluoride was dissolved in 10 mL of deionized water to form an ammonium fluoride solution. The ammonium fluoride solution was slowly added to the mixed solution IV under continuous stirring to form a mixed solution V, and stirring was continued for 0.5 hours. Then, 50 mg of CeO prepared in step (1) was added. 2 The solid powder was added to the mixed solution V to form a light green mixed solution VI. The mixed solution VI was transferred to a high pressure reactor and subjected to a hydrothermal reaction at 120°C for 12 hours. The solid was then collected and washed three times by centrifugation with ethanol, and finally dried in a vacuum oven at 50°C overnight to obtain a brown solid powder Ni 3 Fe 1 -LDH / CeO 2 Nanocomposite materials.
[0042] (4) Preparation of electrode: The glassy carbon electrode was pre-polished and, if necessary, ultrasonically cleaned to remove surface impurities and oil stains. It was named GCE electrode. 3 mg of CeO prepared in steps (1), (2) and (3) was added. 2 Nanowires, Ni 3 Fe 1 -LDH and Ni 3 Fe 1 -LDH / CeO 2 The nanocomposite materials were dissolved in 1 mL of a mixture of ethanol and water with a mass concentration of 0.0001% nafion, with a ratio of ethanol to water of 1:1. The mixture was ultrasonically treated for 30 minutes to prepare a uniform dispersion with a concentration of 3 mg / mL. Then, 3 μL of the above-mentioned different uniform dispersions were drop-coated on the surface of different glassy carbon electrodes and dried at room temperature overnight to obtain different CeO 2 / GCE、Ni 3 Fe 1 -LDH / GCE and Ni 3 Fe 1 -LDH / CeO 2 / GCE electrode.
[0043] The prepared CeO 2 Nanowire powder, Ni 3 Fe 1 -LDH and Ni 3 Fe 1 -LDH / CeO 2 The nanocomposites were observed using a scanning electron microscope. Figure 1 As shown in the SEM image, CeO 2 With obvious linear structure ( Figure 1 (a)), Ni 3 Fe 1 -LDH is a flower-like structure formed by flakes or flakes combined ( Figure 1 (b)), Ni 3 Fe 1 -LDH / CeO 2 Composite nanomaterials are CeO 2 Ni growth on nanowire core 3 Fe 1 -Heterostructure of LDH nanosheets ( Figure 1 (c)). At the same time, the prepared CeO 2 、Ni 3 Fe 1 -LDH and Ni 3 Fe 1 -LDH / CeO 2 Nanocomposites were analyzed using X-ray diffraction (XRD), e.g. Figure 2 As shown, the characteristic crystal planes of each material can be clearly observed in the X-ray diffraction spectrum, indicating that the Ni prepared by the present invention 3 Fe 1 -LDH / CeO 2 The modified electrode material was successful.
[0044] Example 2
[0045] In this example, NiFe-LDH / CeO with different molar ratios of Ni and Fe were prepared. 2 Nanocomposites, and NiFe-LDH / CeO with different Ni and Fe molar ratios 2 Nanocomposite materials were prepared to obtain NiFe-LDH / CeO 2 / GCE electrode, the preparation method is the same as that of Example 1, except that the molar concentrations of nickel nitrate and iron nitrate in the mixed solution IV in step (3) are as shown in Table 1.
[0046] Table 1 Molar concentrations of nickel nitrate and iron nitrate in mixed solution II of Example 2
[0047]
[0048] The three electrode materials prepared in this example are Ni 1 Fe 1 -LDH / CeO 2 Modified electrode materials, Ni 2 Fe 1 -LDH / CeO 2 Modified electrode materials and Ni 4 Fe 1 -LDH / CeO 2Modified electrode materials.
[0049] Example 3
[0050] This example prepared CeO 2 NiFe-LDH / CeO nanowires 2 Composite nanomaterials, and using the above different NiFe-LDH / CeO 2 Nanocomposite materials were prepared to obtain NiFe-LDH / CeO 2 / GCE electrode, the preparation method is the same as that of Example 1, except that in step (3) CeO 2 The amount of nanowire powder used is different, so as to synthesize nanowires containing different masses of CeO 2 NiFe-LDH / CeO nanowires 2 Composite nanomaterials. In this embodiment, CeO 2 The amount of nanowire powder used is shown in Table 2.
[0051] Table 2 CeO in Example 2 2 Amount of nanowire powder
[0052] <![CDATA[CeO 2 Amount of nanowire powder (mg)]]> 30 40 60 70
[0053] Example 4
[0054] A NiFe-LDH / CeO 2 / Preparation method of SPE portable electrode
[0055] Step (1) of this embodiment: CeO 2 Preparation and steps of nanowires (3) NiFe-LDH / CeO 2 The synthesis is exactly the same as that in Example 1. The preparation method of the electrode in step (4) is as follows: using polyvinyl chloride (PVC) as a flexible substrate and a screen printing plate as a mold, a screen-printed electrode (SPE) of a three-electrode system is prepared by a high-temperature ink screen printing process, wherein the working electrode and the counter electrode are carbon electrodes, and the reference electrode is an Ag / AgCl electrode ( Figure 7 a); The SPE electrode pretreatment method is electrochemical treatment, and in 0.1 mol L -1 Cyclic voltammetry was performed in PBS (pH 7.0) solution for 10 cycles at a scan rate of 0.05 V s -1 , the scanning range was 0~1.5V, and then rinsed with distilled water. Then 3μL of 3mg / mL NiFe-LDH / CeO 2 The nanocomposite dispersion (the volume ratio of ethanol to water in the dispersion was 1:1) was drop-coated on the surface of the SPE electrode and dried overnight at room temperature to obtain NiFe-LDH / CeO 2 / SPE portable electrode, in this embodiment, four identical electrode materials were prepared using the same method.
[0056] The various materials and electrodes prepared in Examples 1 to 4 were subjected to relevant performance experiments.
[0057] Take different modified electrodes (CeO 2 (CeO 2 / GCE), Ni 3 Fe 1 -LDH(NiFe-LDH / GCE), Ni 3 Fe 1 -LDH / CeO 2 (NiFe-LDH / CeO 2 / GCE)), in 0.1mol / L KCl and 5mmol / L [Fe(CN) 6 ] 3- / 4- Cyclic voltammetry and electrochemical impedance spectroscopy were used to characterize the electrode modification process in an electrolyte solution composed of Figure 3 a) shows: CeO was modified 2 、Ni 3 Fe 1 -LDH and Ni 3 Fe 1 -LDH / CeO 2 The redox peak current of the cyclic voltammetry curve of the electrode increases successively; Figure 3 b) As shown: CeO 2 and Ni 3 Fe 1 The charge transfer resistance of the electrode modified by -LDH is significantly higher than that of Ni 3 Fe 1 -LDH / CeO 2 The modified electrode is large, indicating that CeO 2 with Ni 3 Fe 1 -LDH composited nanomaterials have enhanced electron transfer capabilities. Figure 3 This shows that the electrode modification process prepared in Example 1 is successful.
[0058] Take different modified electrodes (bare electrode (GCE), CeO 2 (CeO 2 / GCE), Ni 3 Fe 1 -LDH(NiFe-LDH / GCE), Ni 3 Fe 1 -LDH / CeO 2 (NiFe-LDH / CeO2 / GCE)), the glucose to be measured is electrochemically detected to obtain the cyclic voltammogram of glucose. 3 Fe 1 -LDH / CeO 2 After modifying the electrode, the current signal is significantly enhanced and the sensitivity of the sensor is greatly improved. Figure 4 This shows that the electrode modification process prepared in Example 1 is successful and can detect glucose with high sensitivity.
[0059] Take the NiFe-LDH modified electrodes (Ni 1 Fe 1 -LDH、Ni 2 Fe 1 -LDH、Ni 3 Fe 1 -LDH、Ni 4 Fe 1 -LDH), the glucose to be measured is subjected to electrochemical detection to obtain a cyclic voltammogram of glucose. Figure 5 It can be seen that the molar ratio of Ni to Fe is 3:1 (Ni 3 Fe 1 -LDH), the electrocatalytic performance of NiFe-LDH towards glucose is optimal.
[0060] The samples prepared in Example 1 and Example 3 contain different amounts of CeO 2 NiFe-LDH / CeO nanowires (30, 40, 50, 60, 70 mg) 2 The composite nanomaterial electrode is used to perform electrochemical detection on the glucose to be measured, and the cyclic voltammogram of glucose is obtained. Figure 6 It can be seen that CeO 2 When the mass is 50mg, NiFe-LDH / CeO 2 The composite nanomaterial electrode has the best electrocatalytic performance for glucose.
[0061] The detection range of glucose detected by the SPE electrochemical sensor prepared in Example 4 is: Figure 8 The NiFe-LDH / CeO prepared by the present invention 2 / IT curve of SPE electrode after adding different concentrations of glucose. As can be seen from the figure, the peak current of glucose has a good linear correlation with its concentration. The equation is: pa (μA)=2.883+121.732C(μmol / L)(R 2 =0.987), the sensitivity is 1816.89μA·mM -1 cm -2, the detection limit is 0.013 μmol / L. This shows that the electrochemical sensor prepared by the present invention has high sensitivity and low detection limit, and the sensor can be used to sensitively detect glucose.
[0062] Anti-interference ability test of the SPE electrochemical sensor prepared in Example 4, Fig. 9 The NiFe-LDH / CeO prepared by the present invention 2 The it curve of the SPE electrode was added with 0.5mmol / L ascorbic acid (AA), 0.5mmol / L L-cysteine (L-Cystrine), 0.5mmol / L citric acid (CA) and 1mol / L sodium chloride (NaCl) in 0.1mol / L NaOH electrolyte to simulate the real test environment. As can be seen from the figure, after the interfering substances were added, the current value did not change significantly and the current still increased after adding glucose again, indicating that the added interfering substances had no effect on the sensor's detection of glucose. Therefore, this result shows that the prepared electrochemical sensor has good selectivity and anti-interference ability for the detection of glucose.
[0063] Reproducibility and stability verification of the SPE electrochemical sensor prepared in Example 4, Fig.10 Four identical NiFe-LDH / CeO prepared by the present invention 2 / SPE electrode, it can be seen that the peak current of glucose maintains good repeatability. Fig.11 The NiFe-LDH / CeO 2 / SPE electrode stability for glucose detection after 2 days and 7 days, Fig.11 It can be seen that within 7 days, the peak current of glucose maintained good stability, indicating that the prepared electrochemical sensor has good reproducibility and stability.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a NiFe-LDH / CeO2 composite nanomaterial, characterized in that: The NiFe-LDH / CeO2 composite nanomaterial is a composite nanomaterial in which NiFe-LDH nanosheets encapsulate CeO2 nanowires, and the specific preparation method is as follows: (1) Preparation of CeO2 nanowires: Ce(NO3)3·6H2O and NaOH were dissolved in deionized water to obtain Ce(NO3)3·6H2O solution and NaOH solution, respectively. The NaOH solution was slowly dripped into the Ce(NO3)3·6H2O solution under continuous stirring to obtain a mixed solution I. The mixed solution I was subjected to a hydrothermal reaction. After the reaction was completed, the mixture was cooled to room temperature. The solid was collected and washed by centrifugation with ethanol. The obtained solid was then dried and calcined to obtain a white CeO2 nanowire powder. (2) Synthesis of NiFe-LDH / CeO2: nickel nitrate, iron nitrate and urea are dissolved in deionized water to form a mixed solution II; ammonium fluoride is dissolved in deionized water to form an ammonium fluoride solution; The ammonium fluoride solution is slowly added to the mixed solution II under continuous stirring to form a mixed solution III, and stirring is continued. Subsequently, the white CeO2 nanowire powder obtained in step (1) is added to the mixed solution III to obtain a mixed solution IV. The mixed solution IV is subjected to a hydrothermal reaction, the solid is collected and washed by centrifugation with ethanol, and the obtained solid is dried to obtain a brown-yellow solid powder NiFe-LDH / CeO2 nanocomposite material.
2. The method for preparing the NiFe-LDH / CeO2 composite nanomaterial according to claim 1, characterized in that: The molar concentration of Ce(NO3)3·6H2O solution in step (1) is 5-15 mmol / L, and the molar concentration of NaOH solution is 0.3-0.7 mol / L; the volume ratio of Ce(NO3)3·6H2O solution to NaOH solution in mixed solution I is 1:1-1:
5.
3. The method for preparing the NiFe-LDH / CeO2 composite nanomaterial according to claim 1, characterized in that: The conditions of the hydrothermal reaction in step (1) are 100-140° C. for 12-48 hours; the calcination temperature is 300-700° C. for 1-5 hours.
4. The method for preparing the NiFe-LDH / CeO2 composite nanomaterial according to claim 1, characterized in that: In step (2), the total molar concentration of Ni and Fe metal ions in the mixed solution II is 5.4 mmol / L, wherein the molar concentration ratio of Ni ions to Fe ions is 1:1 to 4:1, and the molar concentration of urea is 2.6 mol / L; the molar concentration of the ammonium chloride solution is 2 mol / L; the volume ratio of the ammonium fluoride solution in the mixed solution III to the mixed solution II is 1:1 to 1:7; and the amount of CeO2 nanowire powder added to the mixed solution III is 0.5 mg / mL to 1.17 mg / mL.
5. The method for preparing the NiFe-LDH / CeO2 composite nanomaterial according to claim 1, characterized in that: The hydrothermal reaction conditions in step (2) are 120° C. and the time is 12 h.
6. The method for preparing the NiFe-LDH / CeO2 composite nanomaterial according to claim 1, characterized in that: The drying temperature in step (1) and step (2) is 50°C.
7. Use of the NiFe-LDH / CeO2 nanocomposite material prepared according to claim 1 in the preparation of electrode materials, characterized in that: The NiFe-LDH / CeO2 nanocomposite material is prepared into a dispersion liquid, and the dispersion liquid is evenly dripped onto the surface of an electrode material, wherein the electrode material is a glassy carbon electrode or a screen-printed electrode.
8. The use according to claim 7, characterized in that: The working electrode and the counter electrode of the screen-printed electrode are carbon electrodes, and the reference electrode is an Ag / AgCl electrode. Before drop-coating the dispersion liquid, the screen-printed electrode needs to be pretreated by electrochemical treatment.
9. The use according to claim 8, characterized in that: The electrochemical treatment conditions were as follows: 10 cycles of cyclic voltammetry scanning were performed in 0.1 mol / L PBS (pH 7.0) solution at a scanning rate of 0.05 V s -1 , the scanning range is 0~1.5V, and then rinse with distilled water.
10. Use of the electrode material prepared according to claim 7 in detecting blood sugar.
Citation Information
Patent Citations
Nickel-iron bi-metal hydroxide@ cerium dioxide heterostructure nanosheet material and preparation method and application thereof
CN108447703A
Method for detecting glucose by using novel enzyme-free glucose sensor
CN113092553A
Preparation method and application of cerium dioxide nanoparticle / ferronickel bimetallic phosphide / foamed nickel composite electrode
CN115094456A
Bifunctional electrolyzed water catalyst as well as preparation method and application thereof
CN116905039A